State Islamic University Students’ Perceptions of Israel Affiliated Products: A Study After the Fatwa of Indonesian Ulema Council No. 83 of 2023 Concerning the Law on Support for the Palestinian Struggle - Witro, Doli (Al-Manahij: Jurnal Kajian Hukum Islam, 2024)
This study aims to describe the perceptions of State Islamic University (UIN) students in Indonesia regarding products affiliated with Israel after the issuance of the Indonesian Ulema Council (MUI) fatwa Number 83 of 2023 regarding support for the Palestinian struggle. This research employed qualitative research methods. The primary data of this study were collected through interviews while the secondary data were obtained from scientific articles, books, and so on. The data collection techniques used in this study were observations, interviews, and documentation. The data analysis techniques included data condensation, data presentation, and conclusion drawing. This study found that the overall perception of UIN students towards Israel-affiliated products was the result of a complex interaction between religious values, humanitarian values, solidarity with Palestine, media information, economic considerations, and political awareness. These factors become reinforcements to their agreement and support for MUI’s steps in supporting Palestine. MUI stipulated Fatwa Number 83 of 2023 concerning the Law of Support for the Palestinian Struggle. One of the substances was a call to boycott products that are clearly affiliated with Israel. This boycott has implications for the company’s reduced financial income due to a decrease in product sales turnover. This can paralyze the performance and operations of the company and as a consequence, their assistance to Israel in carrying out attacks on Palestine will be stopped.